Gestão de ativos tecnológicos – estudo sobre os fatores condicionantes de eficácia no processo de licenciamento de tecnologias da Embrapa Instrumentação: a percepção das empresas licenciadas - Pusinhol, Carlos César (Universidade Federal de São Carlos, 2021)
The licensing of technologies developed by Scientific, Technological and Innovation Institutions - STIs for companies is a theme addressed by several studies, as it is one of the traditional forms of technology transfer. It turns out that the main approach in most of the works, was given to aspects that consider the perspective of the STIs. The perspective of entrepreneurs and professionals representing licensed companies, with regard to how to proceed so that the knowledge generated in universities and research centers has increased the possibility of reaching the consumer market, needs to be further understood. This need arises, among other factors, from the differences of interests of the parties, differences in organizational cultures and aspects related to the impacts on the business due to such differences. This study aims to identify the main factors of effectiveness in the technology licensing process from the perspective of representatives of companies licensed by an STI, establishing correlations with the characteristics of the companies and the technical and commercial performance of the licensed technologies. Therefore, it intends to expand the range of knowledge for innovation managers, enabling the strategic implementation of practices that are more appropriate to the reality in which they find themselves, in the search of an increasing in the number of STI technology licenses for companies and success in the commercial exploitation of products, processes, etc., arising from technologies. As a result of the work, it was found that, according to the literature, technology transfer offices play a leading role in the process, but from the perspective of representatives of licensed companies, technology assumes the main role in the licensing process.
Technological asset management - study on the conditioning factors of effectiveness in the technology licensing process of Embrapa Instrumentação: the perception of licensed companies
Keywords: Licenciamento de tecnologia; Instituições científicas e tecnológicas; Eficácia; Inovação aberta; Gestão de tecnologias; Technology licensing; Scientific and technological institutions; Efficacy; Open innovation; Technology management; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INDUSTRIAL::MUDANCA TECNOLOGICA; ENGENHARIAS::ENGENHARIA DE PRODUCAO; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO::INSTITUICOES GOVERNAMENTAIS ESPECIFICAS